Therapeutic Delivery of Butyrylcholinesterase by Brain-Wide Viral Gene Transfer to Mice - Yang Gao; Liyi Geng; Vicky Ping Chen; Stephen Brimijoin (Molecules, 2017)
Recent research shows that butyrylcholinesterase (BChE) is not simply a liver enzyme that detoxifies bioactive esters in food and medications. In fact, in pursuing other goals, we recently found that it has an equally important role in regulating the peptide hormone ghrelin and its impact on hunger, obesity, and emotions. Here, we present and examine means of manipulating brain BChE levels by viral gene transfer, either regionally or globally, to modulate ghrelin signaling for long-term therapeutic purposes and to set the stage for exploring the neurophysiological impact of such an intervention.